Translating cats and cowards - Jacobs, A (Taylor and Francis, 2018)
This essay considers the translatabilty of Trump's language as both a practical and ethical concern. Focusing on the infamous “grab ‘em by the pussy” episode, which occurred during the 2016 U.S. presidential campaign, I examine how the international press translated this phrase and consider the implications of the various translation tactics employed, including the refusal to translate. At issue, I argue, is the principle of accountability and how translation can hold Trump accountable for the language he uses, even when doing so crosses the line.